Fabrication and characterization of shape memory auxetic metamaterial. (January 2023) - Yao, Yongtao; Xu, Yuncheng; Chen, Hao; Kang, Yuying; Liu, Yanju; Leng, Jinsong
The process of repeating shape memory cycle of the shape memory foam whose initial structure is nonauxetic is more complex. In this cases, only one-shot deformation, which will greatly limit the application of this smart metamaterial. Thus, in this study, we report a feasible approach of fabricating the original structure of shape memory foams with auxetic property based on second curing method. The commercial soft polyurethane foam material and shape memory epoxy resin was used in fabricating the shape memory auxetic foam. Polyurethane component plays role in the similar function of "auxetic mold, " while shape memory polymer act as fixing auxetic structure of foam. The negative Poisson's ratio was achieved around −0.22. Tunable foam mechanical property was demonstrated by structural control according to its shape memory property. The functional filler was employed to realize the wireless actuation of auxetic foam. The excellent shape memory properties have been achieved as well. The combination of smart materials and metamaterial structure makes it have excellent structural mechanical properties and intelligent properties of materials, which greatly expands their potential application prospects.